What seems to be the problem officer: A look at burnout and depression among Icelandic police officers. - Hjalti Sigurður Karlsson 1993- (2018)
Depression and burnout are prevalent problems among police officers since their repeated exposure to critical incidents can put them at increased risk of developing these disorders. In this study a questionnaire, comprised of several subscales that measure depression, burnout, perceived stress, social support, as well as resilience, was sent to all working police officers working in Iceland. The purpose of this study was to identify risk factors as well as protective factors for burnout and depression among Icelandic police officers. A total of 301 police officers finished the questionnaire, of those 49 were female. The prevalence of depression in the sample was 17.8% and the prevalence of burnout was 34.0%. Perceived stress had a high positive correlation as well as a high effect on both burnout and depression. Resilience was found to have a buffering effect on perceived stress for both burnout and depression while social support did not have a buffering effect. More research is needed to identify more potential factors that can influence the development of these disorders, and to confirm this buffering effect. Keywords: Depression, burnout, police officers, critical incidents, protective factors, resilience, social support. Þunglyndi og kulnun eru algeng vandamál meðal lögregluþjóna þar sem þeir lenda ítrekað í hættulegum aðstæðum, þessar hættulegu aðstæður geta aukið líkur á þróun þessara sjúkdóma. Í þessarri rannsókn var spurningalisti settur saman úr ýmsum kvörðum sem meta hugtök eins og þunglyndi, kulnun, skynjaða streitu, félagsstuðning og seiglu, og sendur til allra starfandi lögregluþjóna á Íslandi. Tilgangur rannsóknarinnar var að finna áhættuþætti, sem og verndandi þætti fyrir þunglyndi og kulnun meðal íslenskra lögregluþjóna. Alls svöruðu 301 lögregluþjónar, af þeim 49 kvenkyns, spurningalistanum. Alls var algengi þunglyndis í úrtakinu 17.8% og algengi kulnunnar var 34.0%. Skynjuð streita hafði háa jákvæða fylgni, sem og mikil áhrif á bæði kulnun og þunglyndi. Hamlandi áhrif seiglu á skynjaða ...